2002
DOI: 10.2135/cropsci2002.2650
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Sequence Analysis of Markers Tightly Linked to the Soybean mosaic virus Resistance Gene, Rsv3

Abstract: Soybean mosaic virus (SMV) is a major viral pathogen, affecting soybean [Glycine max (L.) Merr.] production worldwide. The Rsv3 gene of soybean confers resistance to three of the most virulent strains (G5-G7) of SMV. The objectives of this study were to map Rsv3 and develop polymerase chain reaction (PCR) based markers for marker-assisted selection (MAS) purposes. Disease-response data were collected from two F(2) mapping populations, L29 (Rsv3) x Lee68 (rsv3) and Tousan 140 (Rsv3) x Lee68 (rsv3). Bulk segrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 34 publications
1
59
0
2
Order By: Relevance
“…SMV has been classified into several distinct strains based on disease reactions on various soybean genotypes910. Genetic mapping studies have identified three distinct R genes ( Rsv1 , Rsv3 , and Rsv4 ) that confer strain-specific resistance to SMV11121314. Extensive studies have identified the SMV effector proteins that interact with each Rsv gene: SMV strain-specific P3 protein is an effector of both Rsv1 - and Rsv4- mediated disease resistance1516 while SMV CI protein is an effector of Rsv3 -mediated ER1718.…”
mentioning
confidence: 99%
“…SMV has been classified into several distinct strains based on disease reactions on various soybean genotypes910. Genetic mapping studies have identified three distinct R genes ( Rsv1 , Rsv3 , and Rsv4 ) that confer strain-specific resistance to SMV11121314. Extensive studies have identified the SMV effector proteins that interact with each Rsv gene: SMV strain-specific P3 protein is an effector of both Rsv1 - and Rsv4- mediated disease resistance1516 while SMV CI protein is an effector of Rsv3 -mediated ER1718.…”
mentioning
confidence: 99%
“…Recently, many molecular markers associated with disease resistance genes have been identified in soybean (Wang et al 2001, Jeong et al 2002. Markers associated with agronomic traits have also been reported in soybean (Yamanaka et al 2001).…”
mentioning
confidence: 99%
“…Contigs and singletons in this work also were identified with similarities to R genes related to virus resistance, such as the KR1, KR4, 3gG2 and Rsv3 mosaic resistance in soybean (Jeong et al, 2002;He et al, 2003;Hayes et al, 2004;Wang et al, 2004), ry-1 resistant to Potato virus Y (Vidal et al, 2002) and N gene for mosaic virus resistance in tobacco and Arabidopsis (Hammond-Kosack and Jones, 1997). In the CitEST, contig 68 shows similarity (1e-44) with the ry-1 (TIR-NBS-LRR) protein.…”
Section: Nbs-lrr Classmentioning
confidence: 81%